Kepuasan Layananan Jaminan Kesehatan Nasional - Agusianita Agusianita; Hasanudin Nuru; Des Metasari (Journal of Telenursing (JOTING), 2023)
This study aims to determine client satisfaction in receiving national health insurance (JKN)/Universal Health Coverage services. This study uses the systematic literature review analysis method, which operates as many as 15 national and international journals uploaded via Google Scholar and PubMed from 2019-2021. Based on research results from 15 journals that have been reviewed, it is known that the decline in services is influenced by the type of country of the JKN client. From the study, information was obtained that there was a decrease in JKN or universal health coverage client satisfaction with an increase in the number of clients in developing countries. In contrast, in developed countries, such as Europe and the Americas, there was an increase in the quality of universal health coverage services. In developed countries, the service is excellent by prioritizing customer satisfaction, whereas, in developing countries, the service seems less good with inadequate service facilities, an overwhelming number of clients, and a small number of health workers and not in proportion to the number of patients. Developing countries have a low level of satisfaction with JKN/universal health coverage services, with a disproportionate ratio of health workers to patients and a significant increase in the number of participants. Keywords: National Health Insurance (JKN), Satisfaction, Universal Health Coverage